Assessment of two portable glucometers and an automated hematology analyzer for the monitoring of diabetes in cat - Sharmin Akter; Tanvir Ahmad Nizami; Kazi Chamonara; Rony Chowdhury; Muhaiminul Islam Tushar (Veterinary Research Notes, 2023)
Objective: The study aimed to assess two portable glucometers and an automated hematology analyzer for monitoring diabetes in cats. Glucose concentrations in the cats' blood samples were determined, and the factors influencing the glucose level were identified in this study. Material and Methods: The study was conducted at the Teaching Veterinary Hospital of Chattogram Veterinary and Animal Sciences University with 30 cats. Blood samples were collected, and their glucose levels were measured using two portable glucometers (Glucotest Prime® and Accu-Chek®) and an automated hematology analyzer (BIOBASE-Silver, BIOBASE). Results: The study showed that local and exotic breeds showed almost the same percentage of diabetes cases with all monitoring devices. Older (Glucotest Prime: before meal = 78.6%, after meal = 85.8%), (Accu-Chek: before meal = 71.5%, after meal = 71.5%), (Hematology analyzer: before meal = 71.5%, after meal = 78.6%), and obese (p = 0.002; before meal = 91%, after meal = 91% with all monitoring devices) animals had a higher occurrence of diabetes than young and non-obese animals. Both male and female cats showed almost equal numbers of diabetes cases. Conclusion: Several factors, like breed, older age, obesity, and gender, are prominent risk factors for diabetes in cats. The study concludes that feline diabetes is of similar concern to human diabe¬tes and can be regularly monitored with a portable glucometer and hematology analyzer. [Vet. Res. Notes 2023; 3(3.000): 11-15]